Stage and tissue-specific expression analysis of two miRNAs and their targets during Solanum betaceum Cav. somatic embryogenesis - Rito, Miguel Ângelo Almeida (2019)
Dissertação de Mestrado em Biodiversidade e Biotecnologia Vegetal apresentada à Faculdade de Ciências e Tecnologia